DAMPAK OVER KAPASITAS DI LAPAS KELAS IIA BEKASI BAGI KEAMANAN NARAPIDANA - Shadiq, Dzaki Zaidan; Gumilar, Gun Gun; Rizki, Mochamad Faizal (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Overcapacity in Class IIA Bekasi Correctional Facility is a serious problem that affects the security of prisoners. This research uses the literature study method to analyze the impact of these conditions. The results of the study show that overcrowding triggers conflicts between prisoners, reduces the effectiveness of supervision, and creates an informal social hierarchy that worsens order and security. These findings emphasize the importance of revamping correctional facilities and policies to create a safe and humane environment for prisoners.